The Effects of Trans-Basin Climate Variability on Skipjack Tuna in the Northwest Pacific Ocean: Causal and Nonstationary - Hou, Xiangyun; Ma, Shuyang; Tian, Yongjun; Zhang, Shaoqing (Frontiers in Marine Science, 2022)
Skipjack tuna (Katsuwonus pelamis, SKJ), a widely distributed and highly migratory pelagic fish, dominates the global tuna catch, especially in the Pacific Ocean, with nearly 70% of world catch. Studies have reported that SKJ in the tropical Pacific was strongly associated with Niño-Southern Oscillations, while the relationship between SKJ in the Northwest Pacific (NWP, the second-contributed statistical area of SKJ Pacific catch) and climate variability has not yet been well understood. Considering the teleconnection between western Pacific and Atlantic Ocean, this study investigates the potential relationship between the relative abundance CPUE (Catch Per Unit Effort) of SKJ and climate indices including trans-basin and basin signals at different spatial-temporal scales in the NWP during 1972–2019 using Convergent Cross Mapping (CCM) and Threshold Generalized Additive Model (TGAM) techniques. Results show the Atlantic Multidecadal Oscillation (AMO) plays a causal role in the temporal SKJ variations with an optimal lag at 15 months, while further analysis preliminarily reveals sea surface temperature acts as a vital medium in the relationship through teleconnection. The AMO effected SKJ processes are nonstationary over the study time, of which the transition years occurred in the early 1990s (around 1991/92). Providing an unprecedented insight into climate variability effect on SKJ in the NWP, this study has essential implications and reference for predicting and managing SKJ fishery through incorporating the climate index in estimating the SKJ abundance in advance, and for the connection between large-migrating species and tans-basin climatic variation.